2015
DOI: 10.1038/bmt.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Unmanipulated haploidentical bone marrow transplantation and post-transplant cyclophosphamide for hematologic malignanices following a myeloablative conditioning: an update

Abstract: This is a report of 148 patients with hematologic malignancies who received an unmanipulated haploidentical bone marrow transplant (BMT), followed by post-transplant high-dose cyclophosphamide (PT-CY). All patients received a myeloablative conditioning consisting of thiotepa, busulfan, fludarabine (n = 92) or TBI, fludarabine (n = 56). The median age was 47 years (17-74); 47 patients were in first remission (CR1), 37 in second remission (CR2) and 64 had an active disease; all patients were first grafts. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 9 publications
12
93
4
4
Order By: Relevance
“…More recently, Bacigalupo et al reported promising results in AML and MDS, especially when Haplo-SCT was performed in CR1. 28 Finally, a CIBMTR registry analysis reported 192 AML patients who underwent PT-Cy Haplo-SCT, with similar outcome but lower chronic GVHD compared with matched unrelated donor Allo-HSCT. 29 Taken together, these results suggest that PT-Cy Haplo-SCT is feasible and effective in high-risk patients with AML or MDS who lack HLA-matched donor.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Bacigalupo et al reported promising results in AML and MDS, especially when Haplo-SCT was performed in CR1. 28 Finally, a CIBMTR registry analysis reported 192 AML patients who underwent PT-Cy Haplo-SCT, with similar outcome but lower chronic GVHD compared with matched unrelated donor Allo-HSCT. 29 Taken together, these results suggest that PT-Cy Haplo-SCT is feasible and effective in high-risk patients with AML or MDS who lack HLA-matched donor.…”
Section: Discussionmentioning
confidence: 99%
“…Umbilical cord blood recipients received CyA 1 mofetil-mycophenolate (MMF) and ATG. Recipients of haploidentical (HAPLO) grafts were given CyA from day 0, MMF from day 11, and CY 50 mg/kg on days 13 and 15 [34].…”
Section: Methodsmentioning
confidence: 99%
“…Most publications are mostly from single center studies on various, usually heterogenous, hematologic diseases. 6,8,9,19 However, there is no consensus on the GvHD prophylaxis regimen in the setting of non-T-cell depleted Haplo-SCT using bone marrow (BM) or peripheral blood stem cells (PBSC). The current study aimed to compare these two approaches for GvHD prophylaxis in patients with acute myeloid leukemia (AML) in complete remission (CR) reported to the European Group for Blood and Marrow Transplantation (EBMT) registry.…”
Section: Introductionmentioning
confidence: 99%